Anxiety and Perceived English and French Language Competence of Education Students - Montgomery, Cameron; Spalding, Thomas (Canadian Journal of Higher Education, 2005)
The authors examined manifest anxiety and perceptions of English and French language competence among Anglophone (n = 35), Francophone (n = 29), and Mixed-heritage (n = 34) elementary education (60%) and secondary education (40%) students (80% female) in their second, third, or fourth year of study at the Faculté Saint Jean (University of Alberta). Participants assessed their language competence differently in English and French. Francophone and Mixed-heritage students felt equally competent in the two languages, but Anglophone students reported much higher language competence in English. Manifest anxiety and self-assessments of language competence were related only among the Anglophone group, with high levels of manifest anxiety associated with both low self-assessments of French language competence and high self- assessments of English language competence—the two being correlated with each other.